Evaluation of errors during different phases of coronavirus disease 2019 TrueNat testing in a tertiary care hospital - Goyal, Nisha; Sharma, Abha; Loomba, Poonam; Mishra, B; Thakur, Archana (Eastern Journal of Medical Sciences, 2020)
Background: Although diagnostic errors have always significantly attributed to clinical and economical losses, now in the ongoing coronavirus disease 2019 (COVID-19) pandemic, the impact of these errors has unquestionably increased multifold. In the present scenario, reporting of false-negative or false-positive test results may adversely affect the public health measures and government restrictive policies, established for the containment of COVID-19 in addition to enhancing the individual suffering and economic burden. The only way to reduce errors in various phases of COVID-19 testing is to evaluate them thoroughly and subsequently follow them up with effective corrective actions. Materials and Methods: The present study was conducted at a tertiary care center, approved by Indian Council of Medical Research for COVID-19 TrueNat testing. Information regarding errors and subsequent corrective actions in preanalytical, analytical, and post-analytical phases of TrueNat testing for COVID-19 were collected. Results: A total of 112 testing errors were observed in the TrueNat testing of 1108 samples during the study duration. Around 58.93% errors occurred in the preanalytical phase of TrueNat testing, followed by 39.29% and 1.79% errors in the analytical phase and post-analytical phases, respectively. Poor quality samples constituted the predominant cause of error in the preanalytical phase. Conclusion: Delivery of accurate results is of paramount importance in this COVID-19 pandemic. A thorough analysis of the various phases of COVID-19 testing will help identify and understand the errors and implement effective corrective actions.